Teaching and Learning Process of English Speaking Skills at SMKN 27 Jakarta Pusat Majoring in Tourism – A Case Study - Mia Utami Putri; Ratna Dewanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat dan Program Studi Pendidikan Bahasa Inggris Fakultas Bahasa dan Seni Universitas Negeri Jakarta, 2020)
Students of tourism vocational schools require mastering speaking skills in English to be able to handle guests from various backgrounds. Yet, the preliminary research showed that 60% of students in SMKN 27 Jakarta Pusat could not speak English fluently. This study aimed at describing the design, teachers' plan, teaching methods, materials, teachers' role, and students' role, and assessment techniques of English speaking teaching and learning. This study used a case study with observation and interview as the research technique. The findings of this study showed that the syllabus design used in SMKN 27 was a functional-based syllabus that was suitable for the vocational high school students. The teaching methods used in teaching and learning were the Direct Method and Audiolingual Method. The materials used by the teachers in teaching and learning process were videos and an English coursebook in most of the observations' meetings. Teachers acted as a prompter and a feedback provider, helped the students when they found any difficulties in expressing themselves using the target language and gave feedback directly. The assessment techniques used were summative and formative assessment and the teachers used mid-term test and final-term test as the assessment techniques.